Standardization of medicines and their impact on hospital pharmaceutical care and drug costs - Duarte, Guilherme Benigno Magalhães (2021)
Introduction: The Hospital Pharmacy (FH) is a clinical, administrative and economic unit, run by a pharmacist, hierarchically linked to the direction of the hospital or health service and functionally integrated with the other administrative and patient care units. Thus, the hospital pharmacy must develop clinical and management-related activities. Methodology: This is a descriptive and exploratory field research with a qualitative approach that was carried out in the hospital pharmacy of the regional hospital of Conceição do Araguaia (HRCA) in which there was an interview directed to the technical responsible pharmacist using a questionnaire with questions that aim to achieve the objectives of this work. Results and discussion: The answers given by the pharmacist in the interview were compared with data found in the available literature on the subject, for this, data from articles published in the last 5 years, that is, from 2017 to 2021, were used. Final considerations: A FH is a sector that demands self-budgetary amounts, making people responsible for the institution adopt methods that ensure greater control over the hospital's bills. The CFT is a multi-professional board responsible for selection, standardization and other issues related to drugs and is important in the drug standardization process. Although the HRCA does not have a CFT to carry out the standardization of medicines, it is still possible to carry out this activity without the need for a commission.